Whom should we fund? A multi-site study of program adaptation, implementation and persistence in a public agency grants program - Karl E. Umble (Adult Education Research Conference, 1994)
The Division of Health Education of a state health department evaluated its replication grants for program adaptation, implementation and persistence. Findings have implications for grantmaking programs and agencies promoting program implementation and maintenance within host organizations.